The modulating effects of propofol and its lipid carrier on canine neutrophil functions - SATO, Reeko (J Vet Med Sci, 2016)
Propofol (2,6-diisopropylphenol), being used as an intravenous sedative and anesthetic agent, influences not only upon nervous system but also for host inflammatory response through modulating neutrophil functions. This study is designed to evaluate the modulating effects of propofol and its lipid carrier administration at clinically relevant rate on canine neutrophil functions. Clinically healthy beagle dogs were received propofol (8.8 mg/kg) from cephalic vein and maintained with propofol dropping infusion (26.4 mg/kg/hr). Blood samples were collected from the dogs before infusion and 30 min after the start of propofol administration, and neutrophil functions were evaluated. The dogs were also administered lipid carrier, and neutrophil functions were evaluated in the same manner as propofol administration. Peripheral white blood cell and neutrophil counts decreased after the propofol or lipid carrier administration. The administration of propofol or lipid carrier significantly reduced neutrophil adherence ability. The superoxide production of neutrophils was measured by luminol-dependent chemiluminescence response using with opsonized zymosan. Peak height of neutrophil chemiluminescence curve was reduced by propofol and lipid carrier administration, on the contrary, peak time of neutrophil chemiluminescence curve was delayed. Administration of propofol or lipid carrier also reduced neutrophil adherence ability to nylon fibers. In the present study, we showed the modulating effects of propofol and its lipid carrier on canine neutrophil functions. However, there was no significant difference in the modulating effects between propofol group and lipid carrier group. Therefore, the modulating effects observed here were deeply concerned in lipid carrier administration.